Decaying Uncertainties: Exploring the Role of Decay Rate Variability in Marine eDNA Dispersal Using Lagrangian Transport Modeling - Mohamed Yosri Zanni; Verena M. Trenkel; Robin Faillettaz (Environmental DNA)
ABSTRACT Environmental DNA (eDNA) has emerged as a powerful tool for fisheries management and biodiversity monitoring, offering novel insights into marine ecosystems. However, linking eDNA concentrations to species abundance remains a significant challenge. Limited understanding of the biotic and abiotic factors influencing eDNA production, decay, and transport in marine environments continues to hinder its broader application. This study aims to address these gaps by modeling eDNA decay and transport dynamics using a Lagrangian particle tracking model, the Connectivity Modeling System. Specifically, we (1) fitted and implemented five temperature‐dependent decay rate relationships and (2) simulated eDNA transport accounting for temperature‐dependent decay rate variability. We modeled eDNA dispersal at three contrasting locations in the Bay of Biscay, Northeast Atlantic, over a full year under the five decay rate scenarios. For eDNA transport, current velocity was the most important factor, followed by the decay rate relationship, while the converse effects were found for eDNA dispersion and lifetime. Temperature was found to have the least impact on transport variability. On average, eDNA persisted between 5 and 30 h, with transport distances varying between 0.3 km and 39.1 km, depending on location, month, decay rate, and depth. Our results emphasize the need for precise decay rate estimates, tailored to species‐specific and encountered temperature conditions, to enhance the power of eDNA‐based monitoring.